Pendidikan Kesehatan Reproduksi pada Remaja - Dian Permatasari; Emdat Suprayitno (Poltekkes Kemenkes Surakarta, 2021)
Background: Reproductive health has the concept that everyone can have a satisfying and safe and responsible sex life. Therefore,it is the right of every teenager to be informed and have acces to true,complete and honest reproductive and sexsual health. The main objective of reproductive health is to provide comprehensive reproductive health services to individuals and their partners, especiallyto adolescents so that each individual is able to purpose is to undergo the reproductive process. Methods: The method used in this community service uses counseling or socialization directly to the target, namely teenagers. Its specific purpose is to protect adolescents from the risk of early marrieage, unwanted pregnancy, abortion, Sexually Transmitted Infection (STIs), HIV/AIDS and sexual violence. Results: The results showed that health counseling on reproductive health for adolescents in Nambakor village, sumenep regency was going well and carried out according to the goals and teenagers were very enthusiastic about participating in the counseling and very benificial for adolescents and the community. Conclusion: Suggestions are expected to be additional information regarding the importance of promotive, preventive, curative efforts in this case the importance of knowledge of productive health.